Factors affecting long-term outcome in dorsal root entry zone lesioning for brachial plexus avulsion. Issue 5 (23rd May 2023) - Du, Tao; Ji, Fan; Ni, Bing; Liu, Ruicun; Shu, Wei; Zhang, Xiaohua; Zhu, Hongwei; Tao, Wei; Hu, Yongsheng; Li, Yongjie
Abstract : Among patients with brachial plexus avulsion, dorsal root entry zone lesioning was less effective for shorter pain duration and phantom limb sensation, but partly changed the phantom limb sensation. Abstract: Dorsal root entry zone (DREZ) lesioning is a classical and effective treatment for brachial plexus avulsion (BPA). However, because of a limited number of cases reported in the literature, the factors affecting surgical outcomes are not known. Furthermore, whether this ablative procedure in the spinal level can change the status of phantom limb pain (PLP) and phantom limb sensation (PLS) is unknown. We retrospectively reviewed the patients with preganglionic BPA who underwent DREZ lesioning at a single center. Patients' baseline characteristics and long-term pain and complications were collected. Postoperative changes in PLP and PLS were recorded. Kaplan–Meier analysis was used to evaluate pain-free survival. Multivariate Cox regression analysis was performed to identify factors affecting pain outcomes. A total of 112 patients met the study inclusion criteria. With an average (range) follow-up of 47.4 (10-134) months, the long-term effectiveness and complication rate were 82.1% and 25.9%, respectively. Of 37 patients (33.0%) who developed PLS, 67.6% (25/37) experienced pain relief, whereas in 45.9% (17/37), PLS disappeared or changed after DREZ lesioning. Multivariate analysis showed that patients with shorter pain duration (≤5 years) and PLS had worse pain outcomes. This study revealed factors that predict the pain outcome of DREZ lesioning based on a large series of cases. The diverse postoperative changes in phantom limb indicate that the mechanisms underlying PLS and PLP at the spinal or supraspinal level may vary among patients with BPA. Future studies should investigate the contribution of maladaptive brain plasticity to the outcomes of patients undergoing DREZ lesioning.